Om de wereld in 50 concerten - Honigmann, Heddy; Giltay, Goert (Cinemien, 2014)
To celebrate its 125th anniversary in 2013, the prestigious Royal Concertgebouw Orchestra traveled the world, performing 50 concerts on six continents. Heddy Honigmann followed the symphony orchestra to Buenos Aires, Soweto and Saint Petersburg. Long tracking shots made in those cities are linked to other important characters in the film: the concertgoers, for whom music is a great passion, a source of happiness, joy and melancholy. For both the musicians and the audience, music is a catalyst for emotion and memory. Honigmann's contemplative style reveals the boundless passion and love for music of the professional musicians, their appreciative audiences and the filmmaker herself; music touches everyone, from every culture, right in the heart. Members of the orchestra and the audience talk about their musical experiences and how they have enriched their lives. There are discussions on inspiration, solace and the power of art, which is always stronger than politics. Footage of concerts and well-oiled rehearsals is interspersed with moments of silence: solitude in a hotel room, interminable flights and - at times difficult - conversations with family and friends at home. The liberally used, beautifully performed pieces of music from composers such as Stravinsky, Brahms, Mahler, Rachmaninoff and Tchaikovsky throw a sensitive light on the experiences of the various protagonists. [www.idfa.nl]